2020
DOI: 10.3390/ijerph17051706
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Health Factors and Its Correlations in Elderly Wheelchair Users Who Live in Nursing Homes

Abstract: Background: The aging is a multi-faceted process comprising both—the physical and mental alterations. Thus, the aim of the study was to evaluate the variables affecting the psychophysical state of the elderly people using wheelchairs and living in nursing homes (NH). Methods: 165 older wheelchair users were included in the study after meeting the inclusion criteria and expressing written consent. The assessment involved cognitive functioning, depression, body balance and flexibility, lung capacity and upper li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…The passage of time and aging lead to the appearance of multiple chronic pathologies, which in turn lead to physical deterioration and the fear of falling down. This fear of falling implies a greater loss of autonomy, a worsening of previous chronic pathologies, and a greater dependence when carrying out the basic activities of daily life, which favors social isolation, cognitive problems, and the appearance of pathologies such as depression [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The passage of time and aging lead to the appearance of multiple chronic pathologies, which in turn lead to physical deterioration and the fear of falling down. This fear of falling implies a greater loss of autonomy, a worsening of previous chronic pathologies, and a greater dependence when carrying out the basic activities of daily life, which favors social isolation, cognitive problems, and the appearance of pathologies such as depression [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Music therapy provides beneficial effects with regard to depressive symptoms, helping to reduce anxiety [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maybe in the beginning, the elderly were not able to do the activities that require muscle strength, self-balance and manual dexterity (e.g, long walks while shopping, heavy domestic chores, stairs climbing the stair, clipping toenails or reaching the most distal part of the body). These elderly might stay independent the longest in the context of in which involves fitness of upper body (having their meals, maintaining basic personal hygiene) [23].…”
Section: Lack Of Movement/exercisementioning
confidence: 99%
“…Specifically, the burden of polypharmacy has been related to financial loss due to (1) greater health care costs, (2) adverse drug events (ADEs), (3) unnecessary druginteractions, (4) medication non-adherence, (5) diminished functional capacity due to medication and (6) multiple geriatric syndromes related to polypharmacy. Actually, well-designed interprofessional intervention that focus on enrolling high-risk older patients with polypharmacy have shown that this multi-disciplinary approach can be effective in improving the overall quality of prescribing, preventing polypharmacy and its effect with mixed results on further health outcomes [1,2,23,24].…”
Section: Overmedication or Uncontrolled Medication (Eg Related To Their Comorbidities)mentioning
confidence: 99%
“…Physical deterioration occurs in many cases, in addition to the worsening of chronic pathologies, due to fear of falling, loss of muscle strength or pathologies that affect mobility. This causes many elderly people residing in nursing homes to decide to use wheelchairs, and this, in turn, further worsens their situation, causing greater difficulty in performing activities of daily living, helping the emergence of pathologies such as depression [30].…”
Section: The Health Of Institutionalized Elderly Peoplementioning
confidence: 99%